SYMBOLIC AND LANGUAGE GAME TRANSLATION POSSIBILITIES: INTERPRETATIVE SENSEDERIVATION - Sergey N. Bredikhin (Вестник Северо-Кавказского федерального университета)
The aim of this study is to analyze the phenomenon of language games and symbol in the process of sense derivation in the original texts and the most efficient possibilities of sense transaction in the receiving linguoculture. The analysis is based on the principles of noematic and phenomenological reflection as a basis for sense decoding.